2021
DOI: 10.2147/cpaa.s266223
|View full text |Cite
|
Sign up to set email alerts
|

Guselkumab for the Treatment of Palmoplantar Pustulosis: A Japanese Perspective

Abstract: Palmoplantar pustulosis (PPP) is a chronic inflammatory disorder characterized by sterile pustules predominantly involving the palms and soles. PPP is refractory to various therapies such as topical ointment, oral medicine, and phototherapies. Pustulotic arthro-osteitis (PAO) is a major comorbidity of PPP that severely impairs patients’ quality of life. Recently, guselkumab, a monoclonal antibody against IL-23, has been available for the treatment of PPP in Japan. The purpose of the present review is to descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…With regard to inflammatory cytokines, psoriasis is associated with elevated levels of TNFα, IL-23, and IL-17, with these cytokines also having a significant impact on bone erosion in psoriatic arthritis ( 60–62 ). In addition, highly effective antibody therapies (biologics) targeting these cytokines have been developed, with a growing list of new inhibitory antibodies being investigated ( 60 , 61 ). Inflammatory cytokines such as TNF-α, IL-6, and IL-17 are also implicated in chronic urticaria ( 53 ), atopic dermatitis ( 63 ), and bullous diseases ( 64 , 65 ).…”
Section: Crosstalk Between the Skin And Bonementioning
confidence: 99%
“…With regard to inflammatory cytokines, psoriasis is associated with elevated levels of TNFα, IL-23, and IL-17, with these cytokines also having a significant impact on bone erosion in psoriatic arthritis ( 60–62 ). In addition, highly effective antibody therapies (biologics) targeting these cytokines have been developed, with a growing list of new inhibitory antibodies being investigated ( 60 , 61 ). Inflammatory cytokines such as TNF-α, IL-6, and IL-17 are also implicated in chronic urticaria ( 53 ), atopic dermatitis ( 63 ), and bullous diseases ( 64 , 65 ).…”
Section: Crosstalk Between the Skin And Bonementioning
confidence: 99%
“…Similarly, smaller studies have reported modest or no clinical benefits with etanercept [ 11 ] and ustekinumab [ 12 , 13 ], and a phase II exploratory study and case studies have shown clinical benefit with apremilast [ 14 , 15 ]. Guselkumab, a monoclonal anti-interleukin (IL)-23 antibody, has shown efficacy in clinical trials and is approved for PPP treatment in Japan [ 16 18 ]. However, the difference between guselkumab and placebo with respect to the least-squares mean change from baseline in Palmoplantar Pustular Area and Severity Index (PPP ASI) score at week 16 of a phase III trial was only − 7.7 (guselkumab 100 mg) and − 4.1 (guselkumab 200 mg), suggesting relatively modest efficacy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to a systematic review, 8 biologics can be effective in both hyperkeratotic PP and pustular PP 9 . Noteworthy, guselkumab, an anti‐IL‐23A monoclonal antibody, was recently approved in Japan for the treatment of pustular PP in patients refractory to previous conventional treatments, after an RCT showed its safety and efficacy at 16 weeks, that was maintained up to 52 weeks 10 …”
Section: Introductionmentioning
confidence: 99%